2020
DOI: 10.3390/ijms21010302
|View full text |Cite
|
Sign up to set email alerts
|

A Single Cell but Many Different Transcripts: A Journey into the World of Long Non-Coding RNAs

Abstract: In late 2012 it was evidenced that most of the human genome is transcribed but only a small percentage of the transcripts are translated. This observation supported the importance of non-coding RNAs and it was confirmed in several organisms. The most abundant non-translated transcripts are long non-coding RNAs (lncRNAs). In contrast to protein-coding RNAs, they show a more cell-specific expression. To understand the function of lncRNAs, it is fundamental to investigate in which cells they are preferentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 198 publications
(228 reference statements)
0
29
0
Order By: Relevance
“…The transcriptional regulation of lncRNAs could be predicted as cis and trans , and could have a positive or negative effect on gene expression [ 7 ]. It is noteworthy that lncRNA regulates the expression of a target gene by cis -regulation, which is restricted to the chromosome from which it is transcribed, while a lncRNA role in trans -regulation is predicted when it affects genes on other chromosomes at the expression level [ 6 , 7 ]. We hypothesized that the DElncRNA target genes could act through cis - or trans -regulating mechanisms, thereby affecting sperm freezability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcriptional regulation of lncRNAs could be predicted as cis and trans , and could have a positive or negative effect on gene expression [ 7 ]. It is noteworthy that lncRNA regulates the expression of a target gene by cis -regulation, which is restricted to the chromosome from which it is transcribed, while a lncRNA role in trans -regulation is predicted when it affects genes on other chromosomes at the expression level [ 6 , 7 ]. We hypothesized that the DElncRNA target genes could act through cis - or trans -regulating mechanisms, thereby affecting sperm freezability.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa comprise a wide repertoire of RNAs that are implicated in several biological processes associated with spermatogenesis, fertilization and embryo development [ 1 , 2 , 3 , 4 , 5 ]. In eukaryotes, the vast majority of gene transcripts are non-coding RNAs (ncRNAs) [ 6 ]. While once thought to be “junk” in the sequences of genomes, accumulating evidence has shown that ncRNAs are implicated in numerous important biological processes, such as transcription, splicing, translation, epigenetic modifications, cell development and differentiation [ 3 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs may regulate gene expression through a number of different mechanisms. These include chromatin remodelling, activation/repression of transcription factors in the nucleus as well as modulation of mRNA/protein stability in the cytoplasm 26,27 . Therefore, the subcellular localization of a lncRNA may provide a reliable indicator of its mechanism(s) of action.…”
Section: Pax6os1/pax6-as1 Modulates the Expression Of Its Target Genementioning
confidence: 99%
“…Well-known and characterized ncRNA classes include ribosomal RNAs (rRNAs) and transfer RNAs (tRNAs), playing pivotal roles in translation. Research focused on other ncRNA classes, such as long intergenic non-coding RNAs (lincRNAs) and microRNAs (miRNAs), have identified that transcripts from these classes serve important regulatory roles in coding transcription [ 11 , 12 ]. Less well characterized ncRNA classes emerge from functional genomic elements, such as enhancer RNAs (eRNAs), promoter proximal transcripts (PROMPTs), or telomeric repeat containing RNAs (TERRAs).…”
Section: Introductionmentioning
confidence: 99%